Where is Uphill? Exploring Sex Differences When Reorienting on a Sloped Environment Presented through 2-D Images. (April 2014) - Nardi, Daniele; Meloni, Roberta; Orlandi, Marco; Olivetti-Belardinelli, Marta
One of the spatial abilities that has recently revealed a remarkable variability in performance is that of using terrain slope to reorient. Previous studies have shown a very large disadvantage for females when the slope of the floor is the only information useful for encoding a goal location. However, the source of this sex difference is still unclear. The slope of the environment provides a directional source of information that is perceived through dissociable visual and kinesthetic sensory modalities. Here we focused on the visual information, and examined whether there are sex differences in the perception of a slope presented through 2-D images with a desktop computer connected to an eye-tracking device. Participants had to identify and point to the uphill direction by looking at different orientations of two virtual, slanted environments (one indoor and one outdoor). Men were quicker and more accurate than women, indicating that the female difficulty with slope emerges at an early, unisensory, perceptual level. However, the eye-tracking data revealed no sex differences in the slope cues used, providing no support to the hypothesis of sex-specific, visual-processing strategies. Interestingly, performance correlated with a test of mental rotation, and we speculate that the disadvantage in mental rotation ability might be an important factor responsible for females' difficulty using slope.